(untitled) (Homiletic, 2023)
There is limited scholarship on African American queer preaching, which may be in part due to homophobia and heterosexism in the Black church. This essay addresses this scholarship gap by providing a rhetorical analysis of a sermon by Bishop Yvette A. Flunder, a Black, same-gender loving congregational pastor. Using the rhetorical analysis modeled by Kimberly Johnson in The Womanist Preacher: Proclaiming Womanist Rhetoric from the Pulpit, I categorize the sermon, “Silent No More,” as a womanist critical engagement sermon and identify accompanying rhetorical tools used by Flunder. Additionally, I argue that the “coming out” motif in the sermon represents queer womanist rhetoric. Through the lens of Yvette Flunder, Black queer preaching is deeply wedded to the African American preaching tradition with the use of lived realities as text, vivid imagery, and the celebratory close. Ultimately, this rhetorical analysis provides insight into the preaching of one of the pioneering Black queer women pastors of the 21st Century.